2014
DOI: 10.1093/comnet/cnu004
|View full text |Cite
|
Sign up to set email alerts
|

On global stability of financial networks

Abstract: Recent crisis in the global financial world has generated renewed interests in fragilities of global financial networks among economists and regulatory authorities. In particular, a potential vulnerability of the financial networks is the "financial contagion" process in which insolvencies of individual entities propagate through the "web of dependencies" to affect the entire system. In this paper, we formalize an extension of a financial network model originally proposed by Nier et al. for scenarios such as t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
8
0
7
Order By: Relevance
“…Incorporating the effect of interdependence into the risk management process has attracted much recent interest (Battiston, Caldarelli, D'Errico, & Gurciullo, 2016;Battiston, Puliga, Kaushik, Tasca, & Caldarelli, 2012;DasGupta & Kaligounder, 2014;Helbing, 2013;Roukny, Bersini, Pirotte, Caldarelli, & Battiston, 2013;Szymanski, Lin, Asztalos, & Sreenivasan, 2015) partly due to the 2007 -2008 global financial crisis and the way in which traditional risk models, also grounded on the assumption of risk independence, failed to foresee it (Battiston, Caldarelli, et al, 2016;Battiston, Farmer, et al, 2016;Besley & Hennessy, 2009;Schweitzer, Fagiolo, Sornette, Vega-Redondo, & White, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating the effect of interdependence into the risk management process has attracted much recent interest (Battiston, Caldarelli, D'Errico, & Gurciullo, 2016;Battiston, Puliga, Kaushik, Tasca, & Caldarelli, 2012;DasGupta & Kaligounder, 2014;Helbing, 2013;Roukny, Bersini, Pirotte, Caldarelli, & Battiston, 2013;Szymanski, Lin, Asztalos, & Sreenivasan, 2015) partly due to the 2007 -2008 global financial crisis and the way in which traditional risk models, also grounded on the assumption of risk independence, failed to foresee it (Battiston, Caldarelli, et al, 2016;Battiston, Farmer, et al, 2016;Besley & Hennessy, 2009;Schweitzer, Fagiolo, Sornette, Vega-Redondo, & White, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…El modelo propone explicar el efecto de contagio combinado dos fases: en la primera de ellas (el choque inicial) se determina la probabilidad de incumplimiento o de quiebra de un banco utilizando el modelo de Merton-Credit-Monitor, que se utiliza como detonador o choque inicial y que determina el número inicial de nodos o bancos afectados. En la segunda fase, a partir del modelo de contagio referido en varios artículos previos, principalmente el de Dasgupta y Kaligounder (2014), se hace una simulación del contagio a los restantes bancos utilizando fundamentalmente el modelo de Erdös-Rényi, donde poco a poco y de acuerdo a una tasa propuesta se va esparciendo el contagio y se va reduciendo el capital de las instituciones afectadas provocando la quiebra o la entrada en default de algunos bancos. El modelo también requiere otros parámetros, como son la proporción de activos externos/activos interbancarios, la proporción capital/activos, el tipo de choque idiosincrático o correlacionado, el grado de los nodos y la distribución homogénea o heterogénea de la red.…”
Section: Introductionunclassified
“…El trabajo comienza con una revisión de los principales trabajos de redes aleatorias, pasando desde el modelo de Erdös-Rényi (1960) y las aportaciones fundamentales de Newman (2003) a la teoría de grafos y redes aleatorias, así como sus trabajos en epidemiología SIR (Newman, 2002). Posteriormente se hace referencia, entre otros, a los trabajos más relacionados con redes aleatorias, como los de Nier y Gai (2010), y los aplicados al caso de México, hasta llegar al artículo de Dasgupta y Kaligounder (2014).…”
Section: Introductionunclassified
“…Many researchers have shown that combining financial and macroeconomic variables to estimate large vector autoregressive (VAR) models produces better forecasts than standard approaches (see, Banbura et al, 2010;Carriero et al, 2013;Giannone et al, 2005;Koop, 2013;Stock and Watson, 2012). Many others, using datasets of a large number of financial institutions, have shown that the financial system has become highly interconnected and thus, can be represented as a network where linkages among agents sharing common structures play a fundamental role in contagion and the spread of systemic risk (see, Billio et al, 2012;DasGupta and Kaligounder, 2014;Diebold and Yilmaz, 2014;Hautsch et al, 2014;Huang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%